Computational intelligence mortality models for the actuary - Willemse Willem Jan (Delft DUP, 2001)
This thesis applies computational intelligence to the field of actuarial (insurance) science. It deals with life insurance where mortality modelling is important. Actuaries use ancient models (mortality laws) from the nineteenth century, for example Gomp
Keywords: Actuarial sciences; Computational intellegence; Mortality forecasts